Between Time and Discourse - Cognola, Federica (Edizioni Ca’ Foscari, 2021)
In this article the different functions of Italian poi are described and analysed from a cartographic perspective. We show that in addition to its use as a temporal adverb (after, then), poi can be used as a temporal or logical connective adverb, as a discourse marker and as a modal particle. These functions can be correlated with different positions in the clause and with differences in the internal structure of the element itself. Finally, we identify the syntactic environments and sentence types in which poi occurs in its function as a modal particle, as well as the special interpretations that are associated with its presence.